Synthesis, characterization and application of Ru(II) complexes containing pyridil ligands for dye-sensitized solar cells - Dayan, Osman; Ozdemir, Namik; Yakuphanoğlu, Fahrettin; Serbetci, Zafer; Bilici, Ali (Paradigm Publishing Services-de Gruyter Brill Sp Zoo, 2020)
In this research, a series of Ru(II) complexes, ([Ru(1-7)(ina)(NCS)2] (1 7=5 [6 (5 mercapto-1,3,4-oxadiazol-2-yl)pyridin2-y1]-1,3,4-oxadiazole-2-thias, ina=isonicotinic acid) were synthesized and characterized using different spectroscopic and analytic techniques, such as NMR, UV, IR, CV and CHN. Also, the new complexes were used in dye-sensitized solar cells (DSSC) as sensitizers. Current-voltage characteristics showed that the modifications of ligands clearly affected DSSC yield. Additionally, DFT calculations were performed and showed locations of frontier molecular orbitals of the complexes. While the locations of HOMO and HOMO 1 orbitals are on Ru(II) metal center and SCN ligands, the location of LUMO and LUMO + 1 orbitals are on the 1-7 ligands.
Keywords: Ru(II) complexes; dye-sensitized solar cells (DSSCs); sensitizer; DFT; current-voltage characteristics